The Role of Stress and Job Satisfaction Among Frontline Nurses in the National Health Insurance Era: The Mediating Role of Self-Efficacy - Adrianto, Ratno; Sumarni, Sumarni; AR, Chaerunnisa (Poltekita : Jurnal Ilmu Kesehatan, 2023)
The study aimed to analyze the effect of role stress (role ambiguity and role conflict) on the self-efficacy and job satisfaction of nurses implementing the National Health Insurance (JKN) era at Panembahan Senopati Hospital, Bantul. The research design used was an analytic survey design using a cross-sectional study approach. The population of this study was all nurses at the Panembahan Senopati Hospital, Bantul, with a sample size of 105 executive nurses. Data analysis used Spearman correlation analysis to see the effect of the independent variables on the dependent variable with a significance limit (α) of 5%. The results indicated no effect of role ambiguity on nurses' self-efficacy in the JKN era at Panembahan Senopati Hospital, Bantul (p=0.236). Further, there was an effect of role conflict on the self-efficacy of nurses in the JKN era at Panembahan Senopati Hospital, Bantul (p=0.000). There is an effect of self-efficacy on the job satisfaction of nurses in the JKN era at Panembahan Senopati Hospital, Bantul (p=0.000). It can be concluded that there is a complex relationship between role ambiguity, role conflict, self-efficacy, and nurse job satisfaction. Although not all relationships have a significant effect, this study provides an initial understanding of the factors that influence the self-efficacy and job satisfaction of nurses at Panembahan Senopati Hospital, Bantul, in the JKN era.